Matrix‐Metalloprotease Resistant Mucin‐16 (MUC16) Peptide Mutants Represent a Worse Lung Adenocarcinoma Outcome. Issue 4 (12th March 2019) - Patel, Jay S.; Callahan, Blake M.; Chobrutskiy, Boris I.; Blanck, George
Abstract : Purpose: The relationship of lung adenocarcinoma (LUAD)–specific proteases and the mutant profile of cytoskeletal and extracellular matrix proteins (CECMPs) are examined. Experimental design: Mutant CECMPs are assessed with an automated application of a protease binding, amino acid–based, scoring database. Results: MUC16 (Human Genome Organization symbol for mucin‐16 gene) mutants in particular are, more often than not, resistant to matrix‐metalloproteases (MMPs) commonly secreted by LUAD cells, and LUAD cases representing the MUC16, MMP resistant mutants have a worse outcome. Similar results are obtained for MUC16 mutants resistant to cathepsins, also commonly secreted by LUAD cells. Analyses also show that MUC16, MMP resistant peptide mutants have greater binding affinities to HLA‐A and HLA‐B when compared to MUC16, MMP nonresistant peptide mutants. Conclusion: These results provide a potential, novel biomarker for lung cancer progression, in particular, protease resistant MUC16 peptides; and suggest a possible mechanism of immune escape entailing the reduction of mutant peptides available for HLA class I binding.